THE ROLE OF CLINICAL PATHWAY IN IMPROVING HOSPITALS COST EFFICIENCY - Taufiqurrahman Taufiqurrahman; Mardiati Nadjib (Proceedings of the International Conference on Applied Science and Health, 2018)
Background: Clinical Pathway (CP) is a method of clinical documentation that reflects clinical practice standards for physicians, nurses and other members of healthcare team. Clinical pathways are collaborative guidelines for treating patients focused on diagnosis, clinical problems and stages of care. The advantage is any intervention given and the development of the patient recorded systematically based on the time criteria set and is expected to improve the quality of service and to lower hospital costs. The aim of this narrative review is to assess the role of CP in improving the efficiency of hospital costs. Methods: Narrative review was performed by analyzing the scientific articles obtained through Electronic Library provided by the University of Indonesia through online database list and chooses Science Direct as a search. The keywords used in the search were "Clinical Pathway and Hospital Cost". Search strategy was conducted by searching for articles related to CP role on hospital cost efficiency. Articles were selected using inclusion criteria and through several stages. Results: Acquired as many as 1.324 articles conducted search through Science Direct. From the results of the screening finally 4 scientific articles were chosen relevant to the topic of writing and the criteria of inclusion or exclusion. After the analysis, it was found that the use of CP in the management of patients can lower hospital costs. Conclusions: Implementation of clinical pathway for the management of patients in hospital can improve hospital cost efficiency.